Comparative Assessment of Growth in Pure and Crossbred Turkeys in a Humid Tropical Environment - Ilori, A.M.; Peters, S.O.; Ikeobi, C.O.N.; Bamgbose, A.M.; Isidahomen, C.E.; Ozoje, M.O. (International Journal of Poultry Science, 2010)
Three hundred poults consisting of 120 local, 120 local x exotic crossbred and 60 exotic poults were generated from matings between indigenous and exotic turkeys. Feed and water intake, body weight and other linear body measurements were evaluated on weekly basis. These were used to compare the performance of pure and crossbred turkeys raised under natural heat stress environment. Growth parameters studied were significantly affected by turkey genotype (p<0.01). At week 20, the exotic turkey had the highest body weight (4484.74±52.07 g) followed by the crossbred (3330.79±34.00 g) and then the local turkey (2869.68±46.08 g). Male turkeys had a higher average body weight of 46.64±0.47 g and 3363.18±72.36 g while the females weighed the lowest (43.31±0.64 g and 3148.92±89.71 g) at weeks 0 and 20, respectively. The crossbreds consumed more feed on the average (14.13±2.02 to 343.00±40.04 g/day) as compared to the exotic and local turkeys. Also on the average, the local turkey had the highest feed efficiency followed by the exotic and then the crossbreds, implying that the higher the feed intake needed to achieve a proportional increase in body weight, the lower the feed efficiency obtained. The crossbreds drank more water (31.56±1.49 to 574.11±141.25 ml) than the exotic and local turkeys. It can therefore be concluded that variations in the genetic make-up of the turkeys accounted for the observed differences in growth and efficiency of feed utilization.